LINGUISTICS OF SAYING - del Castillo, Jesus Martinez (European Scientific Journal, ESJ, 2014)
Linguistics of saying studies language in its birth. Language is the mental activity executed by speaking subjects. Linguistics of saying consists in analyzing speech acts as the result of an act of knowing. Speaking subjects, speak because they have something to say; they say something because they define themselves before the circumstance they are in; and this is possible because they are able to know. Speaking, then, is speaking, saying and knowing. In this sense there is a progressive determination. Knowing makes possible saying, and saying determines speaking. The problem thus is to determine the linguistic intention of the individual speaker to say something in every speech act.